Cross-modal neuroplasticity in partial hearing loss: a mini-review - Aguiar, Patricia V.; Preman, Jennifer; Paul, Brandon T. (Frontiers in Neuroscience, 2025)
Sensory loss induces adaptive neural changes in the remaining non-deprived senses, known as cross-modal plasticity. Recent proposals of cross-modal plasticity suggest that it is a top-down, dynamic phenomenon that can occur through the lifespan and is initiated whether sensory loss is total (as in blindness or deafness) or more subtle (mild-to-moderate partial sensory loss). However, it is unclear whether adaptive plasticity differs between total and partial loss, because there is less research on the latter condition. Here we reviewed neuroimaging research on cross-modal plasticity in adult humans with mild-to-moderate hearing loss and compared it to three claims derived from deafness research. First, cross-modal plasticity is thought to involve both intra-modal strengthening of remaining senses and cross-modal recruitment of deprived cortical areas, but we were unable to identify strong evidence of cross-modal recruitment in adults with partial hearing loss. Second, cross-modal plasticity is believed to arise through top-down connections and implicates cognitive function, which agreed with our findings. Third, cross-modal plasticity is believed to enhance perception in the non-deprived senses. No study in our review supported this claim, but it is possible that cross-modal plasticity in partial hearing loss results in stronger modulation of auditory function by intact senses. In addition, many study outcomes in humans with partial loss were inconsistent. Overall, it may be premature to conclude that cross-modal plasticity operates the same for partial and total forms of sensory loss in humans, and we provide several recommendations for testing these claims in future research.